2008
DOI: 10.1002/dev.20352
|View full text |Cite
|
Sign up to set email alerts
|

Larger tonic pupil size in young children with autism spectrum disorder

Abstract: The symptoms of Autism Spectrum Disorder (ASD) have been suggested to manifest from atypical functioning of the autonomic nervous system (ANS), leading to altered arousal and atypical processing of salient stimuli. Coherent with this, persons with ASD show heightened autonomic activity, sleep difficulties, and structural and neurochemical alterations within the ANS. Recently, we observed decreased pupil responses to human faces in children with ASD. In the current study, we found differences in baseline (tonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
116
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 30 publications
14
116
3
1
Order By: Relevance
“…Previous studies of have reported conflicting results, including an early finding of smaller pupils sizes in children with autism during pupillary dilation (Rubin 1961) and more recently a report of larger baseline pupil size in young children between 23 and 70 months of age (Anderson and Colombo 2009). Our finding of a significantly larger between-subject variation of the resting pupil size in the ASD group supports the likelihood that differences in pupil size may be quite heterogeneous.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous studies of have reported conflicting results, including an early finding of smaller pupils sizes in children with autism during pupillary dilation (Rubin 1961) and more recently a report of larger baseline pupil size in young children between 23 and 70 months of age (Anderson and Colombo 2009). Our finding of a significantly larger between-subject variation of the resting pupil size in the ASD group supports the likelihood that differences in pupil size may be quite heterogeneous.…”
Section: Discussionsupporting
confidence: 83%
“…Children with autism showed pupillary constriction in response to human faces, whereas age-matched controls showed pupillary dilation. Recently, Anderson and Colombo (2009) reported that children with autism had a larger static baseline pupil size.…”
Section: Introductionmentioning
confidence: 98%
“…ASD is one of the most prevalent forms of developmental disability internationally, with current estimates at 1 in 68 (Centers for Disease Control and Prevention, 2014). Impairments to attention have often been considered to be associated or comorbid with the disorder (Keehn et al, 2013), although recent research has suggested that attentional abnormalities play more of a primary role in ASD, underlying several core features, including the impairments in emotional regulation Gardner et al, 1992;Anderson and Colombo, 2009;Garon et al, 2009), and in joint attention (Schietecatte et al, 2012;Morales et al, 2000;Mundy et al, 2007), as well as the inflexibility in behaviour (Hutt et al, 1964;Landry and Bryson, 2004;Lovaas et al, 1979;Casey et al, 1993;Townsend et al, 1996Townsend et al, , 2001Senju et al, 2004). Not surprisingly, impairments to the alerting network, the orienting network, and the executive control networks have been reported in ASD (for an overview of atypical attention in ASD using the three network model, see Keehn et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Other data [197] indicated that those with autism performed normally with neutral faces, but were impaired with nonhuman stimuli. Anderson and Colombo [198] reported a larger pupil size at rest but a decreased pupil response to human faces.…”
Section: Visual Disordersmentioning
confidence: 98%